Study of etiology, clinical profile and predictive factors of spontaneous bacterial peritonitis in cirrhosis of liver - Kawale, Juhi B.; Rawat, Kavita J. (International Journal of Research in Medical Sciences, 2017)
Background: Spontaneous bacterial peritonitis (SBP) is one of the potentially lethal complication of liver cirrhosis and is defined as infected ascites in the absence of any recognizable secondary cause of infection. Majority of the SBP cases are caused by organism from the gastrointestinal tract mainly aerobic gram-negative organisms- Escherichia coli being the most common etiological agent. Methods: It was a prospective observational study done over a period of 1 year in a tertiary care hospital. 50 patients from medical and gastroenterology wards were included in the study. Patients above 12 year of age with diagnosed cirrhosis of liver and documented evidence of SBP were included. Pregnant females, patients who refused to give consent, patients with a documented evidence of intra-abdominal source of infection or patients with ascitis due to non-hepatic causes were excluded. Results: The high serum bilirubin and creatinine levels were associated with higher mortality rate. Hepatic encephalopathy is associated with worse outcome. The outcome of the patient in relation to the grades of ascitis, liver enzymes, prothrombin time, international normalised ratio (INR), Child pugh grades, ascitic fluid polymorphonuclear leucocyte count, ascitic fluid culture and blood culture were not statistically significant. Conclusions: A high index of suspicion should exist for SBP in patients with cirrhosis and ascitis. Serum creatinine and bilirubin levels are strong predictors of mortality. Hepatic encephalopathy has a strong association with mortality in patients with spontaneous bacterial peritonitis.